CRIMINAL LAW ASPECT OF IMPORTING COUNTERFEIT BRANDED FASHION PRODUCTS - Ayu Puspita Sari; Toetik Rahayuningsih (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
World trade is very important for the stability of a country. One of the efforts to meet the needs of a country is by importing product. However, many activities for the import of counterfeit branded product costs a loss to the brand rights owner or brand rights holder and also affect the domestic industry, one of them is in the fashion sector. This research is to provide information regarding the criminal law aspect of importing counterfeit branded fashion products. This type of research was the legal research or normative research through statue approach, conceptual approach, and case analysis. The prohibition criminal law aspect regarding counterfeiting of brand was mainly regulated in the Brand Law precisely in Article 90, and Article 91 of the Brand Law while Article 94 of the Brand Law regulated the prohibition of trade for brand infringement result. Article 90 of Brand Law gave a maximum penalty of imprisonment for 5 (five) years and/ or maximum fine of Rp. 1,000,000,000.00 (one billion rupiah) and Article 91 gave a maximum penalty of imprisonment for 4 (four) years and/ or maximum fine of Rp. 800,000,000.00 (eight hundred million rupiah).